Design of a compact multiband circularly polarized antenna for global navigation satellite systems and 5G/B5G applications. Issue 6 (17th February 2020) - Falade, Oluyemi P.; Ur‐Rehman, Masood; Yang, Xiaodong; Safdar, Ghazanfar A.; Parini, Clive G.; Chen, Xiaodong
Abstract: Design of a multiband circularly polarized antenna is proposed in this article. The antenna has a simple and compact form factor by employing single‐feed stacked patch structure. It exhibits good performance at the global navigation satellite system (GNSS) frequency bands of L1, L2, and L5 and cellular communications frequency band of 2.3 GHz. The antenna has a 3‐dB axial ratio bandwidth of 1.1%, 1.0%, 4.1%, and 1.5% at the four operating bands of L1 (1.575 GHz), L2 (1.227 GHz), L5 (1.176 GHz), and 2.3 GHz. The antenna also achieves a gain of more than 2.2 dBiC and efficiency of more than 70% at the four frequencies. A detailed parametric study is carried out to investigate the importance of different structural elements on the antenna performance. Results are verified through close agreement of simulations and experimental measurements of the fabricated prototype. Good impedance matching, axial ratio bandwidth, and radiation characteristics at the four operating bands along with small profile and mechanically stable structure make this antenna a good candidate for current and future GNSS devices, mobile terminals, and small satellites for 5G/Beyond 5G (5G/B5G) applications.